Introduction to Python for kids : learn Python the fun way by completing activities and solving puzzles - Elumalai, Aarthi (Apress, 2021)
Get comfortable with Python, the most popular programming language used right now in machine learning and data science. This book is the perfect blend of education and fun for kids 8 years and above looking to learn one of the easiest languages to develop programs with, most everything from websites to desktop apps to games to AI. It will include 4 big projects (or capstone projects): 3 games with Turtle, Tkinter and Pygame and a desktop app with Tkinter The book starts with an overview of basic programming concepts such as variables, numbers and strings, while creating fun, personalized mini projects like Print your Name and Is your mom tipping enough. It then dives right into Turtle, a Python library custom-made for kids, where they'll learn how to draw, animate, automate and eventually make colorful mini projects based on the Python concepts learned. Once they have built a foundation in programming and the Python language, they will learn all about building desktop apps with Tkinter and games with Pygame. There is also an entire chapter dedicated to more fun puzzles and activities that come with a step-by-step solution, and another chapter with cool ideas for more puzzles and a section that gives them advice on where they can go from there. By the end of this book, kids will learn Python from the inside-out while creating projects that they can showcase. They will develop problem-solving skills along with programming skills while doing the puzzles and activities described in the book. You will: Gain a gentle, but thorough introduction into the world of programming and Python Create programs and solve problems with core Python concepts Build mini projects and capstone projects (showcase worthy) with Turtle, Tkinter an Pygame Develop programming skills while doing the puzzles and activities described in the book.